Communication of Cluster Using Can Bus - Matej Kubis; Miroslav Gutten; Daniel Korenciak; Matus Danko (Communications - Scientific letters of the University of Zilina, 2019)
The paper deals with the communication between the infotainment elements and the drive component of the car using the CAN bus. In the introduction, there is briefly described the communication bus used in cars. It describes its basic features, benefits and utilization. The main task is graphically programmed and builds a dashboard that will resemble to a real dashboard from a Volkswagen Golf 5. Using the dashboard built in LabVIEW, it controls the real dashboard.